Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Melalui Keputusan Pembelian Sebagai Variabel Intervening - Munadia Istiqamah; Satria Tirtayasa; Hazmanan Khair Pasaribu (CERED Indonesia Institute, 2021)
The data analysis used was the Structural Equation Model (SEM) method with the Partial Least Square (PLS) method. The results of this study indicate that: (1) product quality has a significant positive effect on customer satisfaction with a value of 0.588 and a P-value of 0.000. (2). Price has a significant positive effect on customer satisfaction with a value of 0.180 and a P value of 0.013. (3). Product quality has a significant positive effect on purchasing decisions with a value of 0.365 and P-Values of 0.000. (4). Price has a significant positive effect on purchasing decisions with a value of 0.230 and a P-value of 0.008. (5). The purchase decision has a significant positive effect on customer satisfaction with a value of 0.640 and a value of P 0.000. (6). Product quality has a significant positive effect on consumer satisfaction through purchasing decisions with a value of 0.084 and a P-value of 0.016. (7). Price has a significant positive effect on customer satisfaction through purchasing decisions with a value of 0.148 and P-Values of 0.008.